2021
DOI: 10.1101/2021.04.26.441472
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The AP-1 factorsFOSL1andFOSL2co-regulate human Th17 responses

Abstract: Th17 cells protect mucosal barriers, but their aberrant activity can cause autoimmunity. Molecular networks dictating human Th17 function are largely unexplored, and this hinders disease-studies. Here, we investigated the functions of the AP-1 proteins FOSL1 and FOSL2 in inducing human Th17 responses. Transient knockdown and over-expression strategies demonstrated the two proteins to inhibit Th17-cell identity, while revealing a novel cooperativity between their functions. Strikingly, FOSL1 plays different rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 172 publications
(346 reference statements)
0
7
0
Order By: Relevance
“…Prediction models have indicated that interaction partners shared by candidate TFs could facilitate co-operative or competitive tendencies between the factors . Our recent study revealed a functional coordination between FOSL1 and FOSL2 during human Th17 regulation . To investigate whether an interactome-based mechanism regulates this paradigm, we analyzed these factors for their common binding partners.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Prediction models have indicated that interaction partners shared by candidate TFs could facilitate co-operative or competitive tendencies between the factors . Our recent study revealed a functional coordination between FOSL1 and FOSL2 during human Th17 regulation . To investigate whether an interactome-based mechanism regulates this paradigm, we analyzed these factors for their common binding partners.…”
Section: Resultsmentioning
confidence: 99%
“…AP-1 function is highly complex and is systematically regulated at multiple levels, such as, the choice of dimerizing partner, post-transcriptional/translational events, and additional interactions with bZIP or other unrelated proteins. Our recent functional genomics study found FOSL1 and FOSL2 to negatively regulate human Th17 differentiation . To decipher the mechanisms that govern such functions of FOSL proteins, we examined their binding partners using a whole-cell proteomics approach.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations